SupaVenezia From SupaStore: Between Art, Commerce, and Spatial Dynamics - Kassem, Ayman (Interiority, 2024)
This exhibition review reflects on the spatial and curatorial concepts, interior spatial qualities, and precedent design processes of SupaVenezia, which was held at the A plus A Gallery in Venice from 31 August to 25 September 2022. It examines the design of the display system at the exhibition while addressing issues pertaining to domestic, participatory, and white-cube settings. The review explores the intersection of art, commerce, spatial, and displays design dynamics in relation to the manifestation of the SupaStore’s initial curatorial philosophy. Additionally, it reflects on the variety of spatial experiences provided and the manner in which a small-scale local gallery behaves and survives in the shadows of a monumental event—the 59th International Art Exhibition of Biennale Arte 2022, curated by Cecilia Alemani and produced by La Biennale di Venezia 2022—while drawing comparative reflections with similar scenarios such as Berlin Biennale and Documenta in Kassel.